Octyl 2-cyanoacrylate versus conventional suturing of port site skin closure in laparoscopic appendicectomy: a prospective study - Pattanshetti, Swapnil Annasaheb; Gogate, Abhijit S.; Mahalmani, Vidya M.; Rao, Kannikanti Nageswara (International Surgery Journal, 2021)
Background: With rapidly developing minimally invasive surgery, the laparoscopic appendectomy has become a preferred method for appendicectomy. Tissue adhesives have become an ideal alternative to conventional sutures and could possibly become the preferred standard of care in many procedures. However, this concept remains unexplored due to scanty data comparing the use of adhesive glues and sutures. The present prospective study was done to compare octyl-2-cyanoacrylate with conventional suturing of port site wound closure in laparoscopic appendicectomy in terms of wound complications, time taken for wound closure and cosmetic outcome. Methods: 60 patients diagnosed to have appendicitis (acute, chronic and recurrent) undergoing laparoscopic appendicectomy were divided into two groups (group A-octyl-2-cyanoacrylate) and (group B- conventional sutures) with 30 in each group. Time taken for wound closure, Wound complications and cosmetic outcome were compared in both groups. Results: Patient demographics were comparable in both the groups. The complications were significantly lower in group A compared to group B. Mean surgical time for wound closure in group A was less compared to group B (p<0.001). Wound closure using octyl-2-cyanoacrylate had lower rate of complications compared to conventional suturing but results obtained were not statistically significant. No significant difference in cosmetic outcome was noted in both groups. Conclusions: Wound closure using octyl-2-cyanoacrylate required significantly less time for skin closure compared to conventional suturing in patients undergoing laparoscopic appendicectomy. However, wound complications and cosmetic outcome using octyl-2-cyanoacrylate did not show statistically significant results compared to conventional suture.